Juridical Analysis of Implementation of Rights Transfer to Land & Buildings with Sale and Purchase Deed - Mochamad Nurali Zamroni (Sultan Agung Notary Law Review, 2021)
The purpose of this research is to analyze and find out: 1). Implementation of the transfer of rights to land and buildings with a deed of sale and purchase at the Land Office of Grobogan Regency. 2). Obstacles and solutions in the implementation of the transfer of rights to land and buildings with a deed of sale and purchase at the Land Office of Grobogan Regency. The approach method in this research is normative juridical. The data used are primary and secondary data obtained through interviews and literature study, data analysis was carried out by analytical descriptive. The results of the research concluded: 1) The implementation of the transfer of rights to land and buildings with a deed of sale and purchase at the Land Office of Grobogan Regency, which starts with a sale and purchase transaction, after the sale and purchase is achieved, it must be AJB by PPAT and witnessed by the parties. PPAT must check the completeness of data such as certificates, proof of tax payments and complete identity of the parties. Furthermore, the PPAT Deed along with other files such as a registration application letter, land certificate or letter D, girik or other proof of ownership, identity of the parties, NPWP, marriage certificate and proof of payment of PBB tax payments are brought to the Land Office to be registered as a certificate of ownership for new land rights holders. After the registration process, the next step is to wait for data verification from the Land Office for the issuance of certificates. 2) Obstacles in the implementation of the transfer of rights to land and buildings with a deed of sale and purchase at the Land Office of Grobogan Regency, namely there are still many low levels of education, people are reluctant to take care of the transfer of land rights due to the costs which they think are quite high and will only take time. The length of the SOP (Standard Operational Procedure) for the Transfer of Name Certificate process, the lack of counseling given to the community regarding the importance of registering the transfer of land rights due to buying and selling, and land certificates. Solutions that can be done are to provide socialization or publish brochures, improve the performance of the Land Office through courses/training and improve administration because it is an organization of human resources.